Aplikasi E-Comerce Produk UMKM menggunakan Metode Filtrasi Kolaboratif berbasis Mobile - Purba, Pria Mitra; Suendri, Suendri (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
Micro, Small, and Medium Enterprises (UMKM) in Tebing Tinggi City, North Sumatra have great potential to encourage local economic growth. However, most UMKM in this city still face obstacles in marketing their products online. This research aims to develop a mobile-based e-commerce application with a collaborative filtration method for local UMKM to increase sales and turnover. The type of research is Research and Development (R&D) using the waterfall model including requirements analysis, system design, implementation, testing, and maintenance. The data analysis used includes a collaborative filtration method to recommend products to users based on the highest rating of all UMKM products on the application. Needs analysis through observation, interviews, and literature study. Design using UML diagrams. The implementation applies collaborative filtration for product recommendations based on user preferences, and functionality testing using black boxes. This research produces an e-commerce application that can provide product recommendations that are relevant and by user preferences based on the highest rating patterns and similar behavior of other users. Apart from that, this application also runs smoothly without any problems after black box testing.